2009
DOI: 10.5194/angeo-27-1059-2009
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in gravity wave activity at three locations in Brazil

Abstract: Abstract. Using the variance in meteor radar winds as a measure of gravity wave activity, we investigate the temporal variations in gravity waves at three locations in Brazil: São João do Cariri (2005) which makes it possible to separate the zonal and meridional components of the fluctuating wind velocity. We find that the seasonal variation of the fluctuating wind is similar to that of the amplitude of the diurnal tide, showing a predominantly semi-annual variation, stronger at Cachoeira Paulista and Santa M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…Fukuyama (1977), in his statistical study on night airglow emissions around the mesopause region, found fluctuations of 12-, 6-and 4-month periods. A study of seasonal GW activity over the three Brazilian meteor radar sites was also made by Clemesha et al (2009). In their work they analyzed the fluctuating wind velocities related to GW and observed a semiannual oscillation (SAO) in the meridional wind component over CP and SM, agreeing with our results for the variances (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Fukuyama (1977), in his statistical study on night airglow emissions around the mesopause region, found fluctuations of 12-, 6-and 4-month periods. A study of seasonal GW activity over the three Brazilian meteor radar sites was also made by Clemesha et al (2009). In their work they analyzed the fluctuating wind velocities related to GW and observed a semiannual oscillation (SAO) in the meridional wind component over CP and SM, agreeing with our results for the variances (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Placke et al (2011b) in their analysis of GW activity over Andenes (69.3 • N, 16 • E) and Juliusruh (54.6 • N, 13.4 • E) report SAO with maxima around the solstice. As stated earlier, annual and semiannual oscillations in GW activity are anticipated and have been documented in earlier work (e.g., Antonita et al,2008;Clemesha et al, 2009;Mitchell and Beldon, 2009;Beldon and Mitchell, 2009;Senft and Gardner, 1991;Placke et al, 2011b;De Wit et al, 2014b; and references therein); however, this appears to be the first report of a 4-month oscillation in GW momentum fluxes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Apart from this November minimum, the centroid height appears to exhibit a predominantly semi-annual variation, in agreement with Xiong et al (2003). A semi-annual oscillation is likely to be associated with tides and gravity waves (Clemesha et al , 2009. It is possible that the August maximum in centroid height is related to the strong meteor showers that occur in that month.…”
Section: Centroid Heightmentioning
confidence: 99%
“…Antonita et al, 2008;Clemesha and Batista, 2008;Mitchell, 2009, 2010;Clemesha et al, 2009;Fritts et al, 2010aFritts et al, , b, 2012aVincent et al, 2010;Placke et al, 2011aPlacke et al, , b, 2014Placke et al, , 2015Andrioli et al, 2013aAndrioli et al, , b, 2015Liu et al, 2013;de Wit et al, 2014bde Wit et al, , a, 2016Matsumoto et al, 2016;Riggin et al, 2016). This has largely arisen from a need to obtain improved spatial coverage in the parameterization of GWs and their associated momentum transport in climate models of the whole atmosphere (e.g.…”
Section: Introductionmentioning
confidence: 99%